Cinética de hidrólise de GPTS sob estimulação ultrassônica - Paccola, Carlos Eduardo Targa [UNESP] (2013)
The sono-hydrolysis of 3-glycidoxypropyl-trimethoxysilane (GPTS) was studied as a function of temperature and concentration of oxalic acid, as a reaction catalyst, by means of a heat flux calorimetric method. A reaction cell and ultrasound applying device was idealized for this purpose. Ultrasound forces dissolution to start the hydrolysis reaction. Alcohol yielded in the hydrolysis accelerates dissolution and furthermore the hydrolysis rate. The GPTS hydrolysis rates were studied in mixtures with GPTS/water molar ratio of 1:5, varying the oxalic acid concentration to 0.1 M, 0.2M, 0.4M, 0.5M, 0.6M, 0.8M, and 1.0M, by fixing the temperature at 25ºC. The kinetic model which was found better fitting to the rate equations of GPTS sono-hydrolysis was a rate equation model of order 3/4 regarding to GPTS and first order regarding to water. This rate equation model was adopted for the study of the GPTS hydrolysis as a temperature function. The hydrolysis rates were then studied at the temperatures 5ºC, 10ºC, 20ºC, 30ºC, 40ºC, and 50ºC, by fixing the oxalic acid concentration at 0.3M. The hydrolysis rate constants were found to be in reasonable agreement with the Arrhenius equation. An activation energy of ΔE = (20 ± 2) kJ/mol was estimated for the process